Incidence and severity of retinopathy of prematurity in Turkey - (:unkn) unknown (BMJ Publishing Group, 2015)
Background: The purpose of this study was to estimate the current incidence of retinopathy of prematurity (ROP) and the need for treatment in preterm infants in Turkey. Methods: The study included preterm infants who had been screened for ROP between 2011 and 2013 in 49 neonatal intensive care units. Infants with birth weight (BW) ≤1500 g or ≤32 weeks' gestational age and those with BW >1500 g or >32 weeks' GA with an unstable clinical course were included. The incidence of any ROP or severe ROP and treatment modalities were determined. Results: The study population included 15 745 preterm infants: 11 803 (75%) with GA ≤32 weeks, and 3942 (25%) with GA >32 weeks. Overall, 30% were found to have any stage of ROP, and 5% had severe ROP. Severe ROP was diagnosed in 8.2% of infants with BW ≤1500 g and 0.6% of infants with BW >1500 g. Of all infants diagnosed with ROP, 16.5% needed laser photocoagulation, and 20 patients born at >32 weeks' GA required this treatment modality. Vitroretinal surgery was performed in 28 infants with severe ROP: 23 with GA ≤28 weeks and 5 with GA 29-32 weeks. Conclusions: The findings of our study have the important implication that more mature babies are at risk of severe ROP requiring treatment. An effective programme for detecting and treating ROP should be established in Turkey.